Effects of Different Mechanical Surface Enhancement Techniques on Surface Integrity and Fatigue Properties of Ti-6Al-4V: A Review. Issue 6 (2nd November 2019) - Wang, Zi-Meng; Jia, Yun-Fei; Zhang, Xian-Cheng; Fu, Yao; Zhang, Cheng-Cheng; Tu, Shan-Tung
Abstract: Titanium and its alloys are widely used in aerospace, biomedicine, chemical industries, and other fields due to the excellent properties as high specific strength, strong corrosion resistance, and superior biocompatibility. With the development of mechanical industry, especially of aerospace, the higher fatigue performance of titanium alloys is demanded. Generally, fatigue cracking originates from the materials surface, so the surface roughness, residual stress, and microstructure in surface layer are believed to be the dominant factors in affecting the fatigue crack initiation and propagation, as well as the fatigue strength. Thus, by means of the mechanical surface enhancement techniques, the achievement of reducing the surface roughness, introducing the residual compressive stress, improving the surface microstructure and increasing the surface hardness could significantly enhance the fatigue strength. The effects of various mechanical surface treatments, such as deep rolling, shot peening, and laser shock peening, on surface integrity and fatigue properties of Ti-6Al-4V were reviewed in this article. By comparing surface roughness, hardness, residual stress, surface grain size, depth of grain refinement layer, fatigue properties at room and high temperatures, and residual stress relaxation during fatigue of different surface-treated Ti-6Al-4V, the advantages and the limitations of these surface treatments were identified and evaluated.